2009
DOI: 10.1177/0003319709332108
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Function Impairment in Chronic Venous Insufficiency: Effect of Some Cardiovascular Protectant Agents

Abstract: In segments of human varicose veins, endothelial function was assessed by measuring relaxation induced by acetylcholine in noradrenaline-precontracted preparations. In addition, concentration-response curves to acetylcholine were obtained before and after incubation with the arterial endothelium protectant agents captopril, losartan, troglitazone, pravastatin, or simvastatin. The antivaricose agent escin was also tested. Mean acetylcholine-induced relaxation of varicose venous rings was about 13%, approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
1
20
0
6
Order By: Relevance
“…In this regard Migliacci et al demonstrated that subjects with a history of spontaneous thromboembolism display endothelial dysfunction . Our study and previous work demonstrated that saphenous vein insufficiency is associated with a marked endothelial dysfunction . Finally, endothelial dysfunction accelerates the failure of saphenous vein grafts that are implanted in coronary and peripheral bypass surgery .…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In this regard Migliacci et al demonstrated that subjects with a history of spontaneous thromboembolism display endothelial dysfunction . Our study and previous work demonstrated that saphenous vein insufficiency is associated with a marked endothelial dysfunction . Finally, endothelial dysfunction accelerates the failure of saphenous vein grafts that are implanted in coronary and peripheral bypass surgery .…”
Section: Discussionsupporting
confidence: 72%
“…Endothelial dysfunction leads to the development of arterial vessel inflammation, remodeling, and atherosclerosis and, by this means, is significantly associated with an increased incidence of ischemic heart disease, peripheral artery disease, and stroke . However, endothelial dysfunction also appears to contribute significantly to the development of vein‐related diseases . Venous endothelial function is significantly affected by cardiovascular risk factors such as diabetes mellitus and a smoking habit, which are known to impair arterial function and to promote cardiovascular diseases .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The venous endothelium acts in part as a main barrier between blood and vascular tissue. Additionally, it partially prevents the physical injury of the vessel wall by external destructive factors via providing sufficient intravascular volume and maintaining required oxygen delivery [12]. Moreover, endothelial cells are clearly important for angiogenesis, because functional endothelial cell migration is essential for new vessel formation [13].…”
Section: Discussionmentioning
confidence: 99%